Dry-land strength training vs. electrical stimulation in sprint swimming performance - Girold, S.; Jalab, C.; Bernard, O.; Carette, P.; Kemoun, G.; Dugué, B. (The Journal of Strength and Conditioning Research, 2012)
This study was undertaken to compare the effects of dry-land strength training vs. an electrical stimulation program on swimmers. Twenty-four national-level swimmers were randomly assigned to 3 groups: the dry-land strength training program (S), the electrical stimulation training program (ES), and the control (C) group. The training program lasted 4 weeks. The subjects were evaluated before the training, at the end of the training program, and 4 weeks later. The outcome values ascertained were peak torque during arm extension at different velocities (from -60 to 180°/s) using an isokinetic dynamometer and performance, stroke rate, and stroke length during a 50-m front crawl. A significant increase in swimming velocity and peak torque was observed for both S and ES at the end of the training and 4 weeks later. Stroke length increased in the S group but not in the ES group. However, no significant differences in swimming velocity between S and ES groups were observed. No significant changes occurred in the C group. Programs combining swimming training with dry-land strength or electrical stimulation programs led to a similar gain in sprint performance and were more efficient than swimming alone.